2017
DOI: 10.18632/oncotarget.18739
|View full text |Cite
|
Sign up to set email alerts
|

Global DNA hypomethylation in leukocytes associated with glioma risk

Abstract: Global DNA hypomethylation in leukocytes has been associated with increased risk for a variety of cancers. However, the role of leukocyte global DNA hypomethylation in glioma development, if any, is largely unknown. To define this role, we performed a case-control study with 390 glioma patients and 390 controls with no known cancer. Levels of 5-methylcytosine (5-mC%), a marker for global DNA methylation, were measured in leukocyte DNA. Overall, median levels of 5-mC% were significantly lower in glioma cases th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Lower levels of methylation seen in glioblastoma samples were weighted into the younger group with increasing methylation levels with advancing age (Figure A). A global hypomethylated state associated with glioma risk was observed in a previous study in leucocytes 32 . Although regression analysis of increased genomic methylation levels with increasing age did not reach significance by regression analysis, the trend is consistent with hypomethylation in the younger age group, These data provide further evidence regarding the role of genomic hypomethylation in glioblastoma, especially in young patients.…”
Section: Discussionsupporting
confidence: 70%
“…Lower levels of methylation seen in glioblastoma samples were weighted into the younger group with increasing methylation levels with advancing age (Figure A). A global hypomethylated state associated with glioma risk was observed in a previous study in leucocytes 32 . Although regression analysis of increased genomic methylation levels with increasing age did not reach significance by regression analysis, the trend is consistent with hypomethylation in the younger age group, These data provide further evidence regarding the role of genomic hypomethylation in glioblastoma, especially in young patients.…”
Section: Discussionsupporting
confidence: 70%
“…Analysis of global DNA methylation revealed that non-treated HL-60 and Jurkat cells exhibited 2.3% and 2.9% of 5-mC DNA, respectively. The 5-mC levels in primary human fibroblasts ranged from 1.0% to 1.7% ( Maierhofer et al , 2017 ), while the mean 5-mC level was 2.8% in peripheral blood of 100 male workers employed in automotive battery factories ( Devoz et al , 2017 ), 3.82% in leukocytes from 390 volunteers with no known cancer ( Shen et al. , 2017 ), and 2.28% in non-treated LNCaP human prostate cancer cells in vitro ( Wu et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed recruitment method for glioma patients and healthy controls was reported in our previous publication 34 . In brief, a total of 565 glioma patients and 1130 healthy controls were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed recruitment method for glioma patients and healthy controls was reported in our previous publication. 34 In brief, a total of 565 glioma patients and 1130 healthy controls were included in the study. The cases were newly diagnosed histologically confirmed glioma patients seen at The University of Texas M. D. Anderson Cancer Center (MDACC) between April 2014 and July 2018.…”
Section: Study Populationmentioning
confidence: 99%